Implementasi Pendidikan Karakter Islami di MTs Cijawura Kota Bandung - Amalia Nurul Fadilah; Riva Trivani; Ahmad Rizki Fauzi; Cep Indra; Ifah Khadijah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by student character problems that are often carried out in schools, including speaking rudely, borrowing things without being returned, stealing money, behaving disrespectfully to teachers and friends, and not being disciplined when entering school and doing assignments and so on. In addition, students still like to ridicule their peers and upperclassmen who have imperfections in their physicality, appearance, or inadequate academic potential. The purpose of the research is to find out the pattern of character development, habituation patterns, and exemplary practices carried out by school principals and teachers at MTs. Cijawura, Bandung City. The research method used is a qualitative (descriptive) method to find out the data and information needed to support the research in accordance with the previously set goals. The results of the first research, coaching. Principals and teachers always provide guidance in school activities and in daily learning. Second, habituation. Teachers as the vanguard in educating students' character in terms of habituation of daily attitudes. Third, example. The example conveyed to all students is a very fundamental thing in character or moral education. Principals, teachers, and staff always work together to provide exemplary models so that students can imitate the behavior of teachers so that they become good examples.